Utilizing cactus pear pruning residuals as sustainable growing media for containerized basil (Ocimum basilicum L:) cultivation - Nicolò Auteri; Filippo Saiano; Riccardo Scalenghe; Alessandra Carrubba; Mauro Sarno (PLoS ONE, 2025)
The increasing interest in sustainable and cost-effective options for containerized plant cultivation has driven research into the use of agricultural by-products and waste as alternative growing media. Cactus pear (Opuntia ficus-indica (L.) Mill.) pruning residuals, abundant in Mediterranean regions, represent a potential renewable resource. This study aimed to evaluate the suitability of cactus pear pruning residuals, enriched with calcium (Ca²⁺), iron (Fe²⁺ and Fe³⁺) ions, as a growing medium for basil (Ocimum basilicum L.) cultivation, with a focus on plant growth. From pots under greenhouse conditions, growth parameters (plant height, leaf area, number of leaves), chlorophyll content (SPAD), phosphorus availability in substrates (Olsen), and volatile compounds in leaves (HS-SPME coupled with GC-MS) were measured. Results suggest that incorporation of Ca- and Fe-enriched substrates significantly improved basil growth, with leading to better nutrient assimilation and higher growth metrics (plant height +23%; number of leaves +17%; leaf area +67%) compared to the untreated cactus pear substrate. Plants grown in Fe-enriched substrates exhibited increased plant height (+14%), leaf area (+48%), and number of leaves (+14%), along with improved phosphorus availability, compared to Ca2+ enrichments. The addition of 5% Fe3+ enriched cactus pear to the substrate resulted in increased plant height (+20%), number of leaves (+22%), and leaf area (+29%) compared to the control. Cactus pear pruning residuals, when enriched with Fe3+, show significant promise as a sustainable and cost-effective alternative to conventional growing media for basil cultivation, particularly in Mediterranean environments.